PENERAPAN MODEL PEMBELAJARAN PROJECT-BASED LEARNING PADA MATA PELAJARAN SBdP MATERI KERAJINAN IKAT CELUP DI SEKOLAH DASAR - Fahrurrozi; Yofita Sari; Uswatun Hasanah; Adinda Desty Dian Utami (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The Project Based Learning (PjBL) learning model is a student-centred learning model. In this model, students are given a real project to work on. The PjBL model can be applied to the learning subject that has material about daily life, one of them is Art, Culture, and Craft (SBdP) learning subject. The purpose of the study described in this article is to find out how the implementation of the PjBL model in SBdP learning, one of them is derived from Tie-Dye Handicraft learning material. Tie-Dye Handicraft is a craft that produces motifs onthe surface of the clothes. It is applied to see the result of this study whether the PjBL model is effectively applied in learning the material or not. This research was conducted by using qualitative research, library research or literature research. The data were obtained from the research that has already existed on the internet. The results indicated that the implementation of the PjBL model for SBdP learning subject provided positive benefits for students and teachers. In other words, PjBL model could optimize SBdP learning subjects in elementary schools which was especially based on Tie Dye Handicraft learning material.